Summer cooling in the east central Arabian Sea -A process of dynamic response to the southwest monsoon (MAUSAM, 1984)
The cooling of the east central Arabian Sea during summer monsoon season is examined using data sets-of MONEX '79 and MONSOON '77 programmes. These studies have revealed that downward transfer of heat due to the mixing of warm surface and cold sub-surface waters associated with deepening of the current shear zone is the predominant process for the observed cooling in the region. The rate of cooling is greater immediately after the onset of strong monsoon winds and the development of anti-cyc10nic wind stress curl, which give rise to a southerly current off the west coast of India. The downward flux of heat is found to vary in the study area with generally higher values in the western regions where the growth of surface layer is maximum. The cyclone heat potential, during pre-monsoon and monsoon conditions is also studied.